Isolation and Characterization of Subpopulations of Rat Ascites Hepatoma Cell Line of AH109A with Different Metastatic Potentials - Miura, Yutaka (Kluwer Academic Publishers, 2003)
Rat ascites hepatoma cell line of AH109A proved to be divided into two subpopulations with different invasive and metastatic potentials, when cultured in the medium containing allogeneic rat sera. One population adheres to the culture dish, actively extending pseudopodia, and the other remains in a floating state. Utilizing this character, we have separated these two populations. After three successive separation steps, adhesive AH109A cells and floating AH109A cells were obtained. Adhesive AH109A cells proliferated more rapidly and invaded more actively than did floating AH109A cells. Adhesive AH109A cells metastasized mainly to lung, while floating AH109A cells to mesentery, when intravenously injected into tail veins. Histological studies revealed that adhesive AH109A cells showed lymphatic metastases to lung. These results suggest that the two populations separated from parental AH109A cells provide good models for the study of tumor invasion and tissue-specific metastasis and that adhesive AH109A cells can be used for the creation of lymphatic metastasis model of rats.